(3x-36)+(2x+26)=90

Simple and best practice solution for (3x-36)+(2x+26)=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-36)+(2x+26)=90 equation:


Simplifying
(3x + -36) + (2x + 26) = 90

Reorder the terms:
(-36 + 3x) + (2x + 26) = 90

Remove parenthesis around (-36 + 3x)
-36 + 3x + (2x + 26) = 90

Reorder the terms:
-36 + 3x + (26 + 2x) = 90

Remove parenthesis around (26 + 2x)
-36 + 3x + 26 + 2x = 90

Reorder the terms:
-36 + 26 + 3x + 2x = 90

Combine like terms: -36 + 26 = -10
-10 + 3x + 2x = 90

Combine like terms: 3x + 2x = 5x
-10 + 5x = 90

Solving
-10 + 5x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 5x = 90 + 10

Combine like terms: -10 + 10 = 0
0 + 5x = 90 + 10
5x = 90 + 10

Combine like terms: 90 + 10 = 100
5x = 100

Divide each side by '5'.
x = 20

Simplifying
x = 20

See similar equations:

| 2x*2x=10 | | 114-5x=22x+21 | | v*v=W+V | | 5x-0+150=180 | | 6x-4(x-2)=7x(3x-4)+19 | | x^2-12x+77=0 | | 6x+6(2x-5)=-10-2x | | 3x^2-16x+12=0 | | 3y=180 | | (x+40)+(3x-10)=180 | | P+q-p-3q+5= | | 10-7x=106-28x | | 5+7x=11+7x | | 20+5=24 | | 2x-36=100 | | 3(x+3)=(3x+9) | | 30=-11x | | (2x-3)(2x-3)=0 | | 5x-y+150=180 | | -N+(v*b*b)=r | | (x-2)(x+2)=(x-1) | | 2.6z^2-0.9z+2=0 | | m-1=2 | | 5x+12-13= | | 5h-2= | | 141-5x=3x+21 | | -9t-5=-4t+10 | | 6(Z-3)+7Z-3= | | 7x^2-27x-14=0 | | -3X+1=-8X-4 | | -32-4x=8-9x | | a-2=-a-5 |

Equations solver categories